DISTANCE LEARNING: ITS PECULIARITIES IN HIGHER EDUCATION DURING WORLD PANDEMIC COVID-19 - Юлія Заячук; Анастасія Олексишин (National Academy of Educational Sciences of Ukraine, 2022)
The work is devoted to the study of the issue of distance learning as a form of organization of the educational process in higher education. It is noted that distance learning has become one of the answers to the challenges of global reality of pandemic COVID-19. It is shown that distance learning was not a completely new form of organization of the educational process in higher education. Five generations of distance learning in historical retrospect and its characteristics and unique traits are presented. It is highlighted that the current stage of distance learning development can be considered as the next sixth generation, which is directly related to the global reality of pandemic COVID-19. The most important features of distance learning at this stage, namely its massiveness, lack of alternatives, and the improvement of distance education platforms are also presented. Besides an analysis of the experience adopted at different countries concerning the distance learning in the higher education institutions during the world pandemic COVID-19 is done.